Kritik Epistemologis Tafsir Ishari Ibn ‘Arabi - Mufid, Fathul (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2020)
Islamic interpretation is a method of Sufi interpretation based on the intuitive knowledge of a Sufi as a result of spiritual cultivation or riyadlah in climbing Sufistic stations (maqamat). Thanks to the riyadlah their inner eyes (bashirah) become clear so that they are able to capture the special sciences that come directly from Allah SWT. The Qur'an for them, besides having the meaning of zahir also has an inner meaning, which can only be understood by certain people of the Sufis, among whom is a Sufi-philosophical figure from Andalusia (Spain) named Shaykh al- Akbar Muhyiddin Ibn'Arabi. This paper is the result of library research (library research) which aims to criticize the epistemological foundation of Ibn ‘Arabi's interpretation.The approach in this study is a qualitative approach in the collection of data using documentary methods, and the analysis of data using descriptive-analysis methods. The findings of this study are that; a) The epistemology of Ibn Arabi ishari's interpretation is difficult to formulate, both the source, method, and systematics because the basic interpretation used is mystical intuition which is derived from divine inspiration which is subjective so that it appears inconsistent and not systematic. b) Normatively, the interpretation of ishari Ibn ‘Arabi, some of them fulfill the interpretation requirements specified by the scholars, but there are also those who do not meet the requirements, because they use ta'wil which is far from the meaning of zahir and is contradicted by most mufassirs. c) From the perspective of Sufism-Falsafi, Ibn ʻArabi's interpretation is entirely acceptable, given his capacity as a top-level Sufi-philosophy with the predicate khatam al-awliya ’.